2011
DOI: 10.1111/j.1365-2265.2011.04109.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced levels of E-cadherin correlate with progression of corticotroph pituitary tumours

Abstract: Corticotroph tumour progression was associated with reduced expression of the epithelial marker E-cadherin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 30 publications
5
36
0
2
Order By: Relevance
“…By contrast, E-cadherin mRNA levels were significantly reduced in invasive compared with non-invasive GH-secreting tumours. Alteration of E-cadherin expression has been shown in pituitary adenomas (8,19,40), is now well characterised in GH-producing adenomas (8,42,44,45) and is not correlated with pre-operative medical treatment (8). In the present study, we have observed that ESRP1 expression was significantly reduced in GH invasive tumours and E-cadherin expression was positively associated with that of ESRP1.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…By contrast, E-cadherin mRNA levels were significantly reduced in invasive compared with non-invasive GH-secreting tumours. Alteration of E-cadherin expression has been shown in pituitary adenomas (8,19,40), is now well characterised in GH-producing adenomas (8,42,44,45) and is not correlated with pre-operative medical treatment (8). In the present study, we have observed that ESRP1 expression was significantly reduced in GH invasive tumours and E-cadherin expression was positively associated with that of ESRP1.…”
Section: Discussionsupporting
confidence: 48%
“…This process has multiple consequences for the phenotype and behaviour of cells, and constitutes one major aspect of the cancerrelated epithelial mesenchymal transition (EMT) process (18). Epithelial E-cadherin expression has been investigated in several pituitary adenoma subtypes and its alteration could contribute to the invasiveness of pituitary adenomas (8,19,20). In addition, molecular studies have suggested that EMT may play an important role in GH adenoma progression (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…EMT is shown to be of significant importance in the aggressiveness and progression of somatotroph and corticotroph adenomas (15,17,18). However, using our selection criteria, we cannot conclude that EMT is the major component of the tumor growth in gonadotroph adenomas.…”
Section: Discussionmentioning
confidence: 82%
“…Studies of growth hormone and ACTH-producing adenomas have linked EMT to the progression of tumors. The reduction in E-cadherin content in these tumors has been associated with tumor size, invasiveness and poor response to medical treatment (15,17,18,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Qian et al (2007) found a somewhat lower percentage of tumors with reduced E-cadhein expression, 62% of 69 tumors. Evang et al (2011) investigated 48 ACTH-secreting tumors and found that 77% of them had lost or had significantly reduced E-cadherin. Fougner et al (2010) found that the percentage was 47% in GH-tumors ( n = 83).…”
Section: The Rb Connectionmentioning
confidence: 99%